LOW-DENSITY URBANISM. WHAT IS IT? (City: History, Culture, Society, 2018)
An Interview with Bisserka Gaydarska and John Chapman (Durham University, Department of Archaeology, Durham, UK)
Keywords: Gordon Childe; low-density urbanism; archaeology; urban studies